2021
DOI: 10.1002/jsfa.11130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐frying on distribution of protons and physicochemical qualities of mackerel

Abstract: BACKGROUND In this work, low‐field nuclear magnetic resonance (LF‐NMR) and magnetic resonance imaging were used to investigate the changes in protons (from water and oil) distribution of mackerel during the frying process. The relationship between proton migration and some physicochemical indexes was established by partial least squares regression (PLSR). The changing mechanism of the quality characteristics and physicochemical properties of fish meat under different frying conditions was analysed by LF‐NMR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…With the increase of magnetic field intensity, the brightness inside the pseudocolour image gradually increased first and then decreased, and the brightness of the MF-60 was the highest, indicating that there were more muscle water molecules in the shrimp muscle, and the water storage capacity was enhanced. These results may be related to changes in muscle tissue structure and protein-water interaction ( Zhang, Cheng, Wang, Yi, & Li, 2021 ). Cheng, Wang, Yang, Lin, Wang, and Tan (2020) also found that the denaturation of muscle proteins caused by the freezing process leads to the conversion of some immobilised water into free water.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of magnetic field intensity, the brightness inside the pseudocolour image gradually increased first and then decreased, and the brightness of the MF-60 was the highest, indicating that there were more muscle water molecules in the shrimp muscle, and the water storage capacity was enhanced. These results may be related to changes in muscle tissue structure and protein-water interaction ( Zhang, Cheng, Wang, Yi, & Li, 2021 ). Cheng, Wang, Yang, Lin, Wang, and Tan (2020) also found that the denaturation of muscle proteins caused by the freezing process leads to the conversion of some immobilised water into free water.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in protein content was found in the Carimañolas during the frying process; this is due to the fact that proteins denature when exposed to temperatures above 65°C, and consequently, their biological value decreases drastically [ 42 , 43 ]. Table 3 shows that the percentage of proteins was higher with the increase of the frying temperature for the types of frying; these results agree with what was indicated by [ 44 , 45 ] who reported that as the temperature increased, the protein increased; the authors justified that the result is due to the loss of humidity of the product; and this causes a concentration of solutes.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) was measured according to the previously reported method of Zhang et al ., 17 with minor modifications. About 3 g of krill sample was put into a round capsule, and each sample was placed on a 60 mm diameter sample chamber for MRI measurement.…”
Section: Methodsmentioning
confidence: 99%